2019
DOI: 10.1029/2019gl085409
|View full text |Cite
|
Sign up to set email alerts
|

Energy Conversion and Dissipation at Dipolarization Fronts: A Statistical Overview

Abstract: Dipolarization fronts (DFs) are important for energy conversion, particle acceleration, and flux transport in the magnetotail. The partition of energy conversion between ions and electrons and the energy dissipation at DFs are not well understood. In this paper, we present a statistical study of energy conversion and dissipation of 122 DFs observed by Magnetospheric Multiscale mission in the magnetotail. Statistically, electromagnetic energy transfers to plasma at DF. The released energy is mainly transferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 61 publications
(117 reference statements)
13
65
0
Order By: Relevance
“…Journal of Geophysical Research: Space Physics is comparable with ion dissipation in some events (Figure 5j), but its average effect along downtail direction is more insignificant than that of ions (Figure 5i), which is consistent with recent MMS observations (Zhong et al, 2019). Based on magnetohydrodynamic (MHD) simulation, Birn and Hesse (2005) showed that load regions expand azimuthally and dissipation becomes stronger in the near-Earth region (see Figure 7 in their paper).…”
Section: 1029/2020ja028568supporting
confidence: 85%
See 2 more Smart Citations
“…Journal of Geophysical Research: Space Physics is comparable with ion dissipation in some events (Figure 5j), but its average effect along downtail direction is more insignificant than that of ions (Figure 5i), which is consistent with recent MMS observations (Zhong et al, 2019). Based on magnetohydrodynamic (MHD) simulation, Birn and Hesse (2005) showed that load regions expand azimuthally and dissipation becomes stronger in the near-Earth region (see Figure 7 in their paper).…”
Section: 1029/2020ja028568supporting
confidence: 85%
“…Many researches have suggested that huge amounts of energy stored in the magnetic field are converted into plasma at the DF (S. Y. Huang, Fu, et al, 2015;Khotyaintsev et al, 2017;Zhong et al, 2019). The global effect of this conversion is even comparable to the reduction of the global magnetotail flux during intervals of geomagnetic activity (Angelopoulos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large amount of magnetic energy is transferred to plasma ( J · E > 0) at DFs (Angelopoulos et al, 2013; Huang et al, 2012, 2015; Zhong et al, 2019). The released magnetic energy can heat and accelerate particles, which results in the enhancement of plasma temperature and high‐energy electron/ion flux frequently observed at/behind DFs (Deng et al, 2010; Fu et al, 2011, 2012; Ohtani et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Observations of a dipolarization front by MMS on 24 June 2017 (adapted from Zhong et al, 2019). Panels (a)–(d) show the variations of B z component in GSM coordinates observed by MMS1, MMS2, MMS3, and MMS4, respectively.…”
Section: Application: Determining the Geometry Of The Magnetotail Dfsmentioning
confidence: 99%